TRADITIONALISM OR MODERN IN ROMANIAN MANAGEMENT ACCOUNTING? - SIMIONESCU, Silvia; BICĂ, Elena; BOGDĂNOIU, Cristiana Luminița (Theoretical and Practical Research in Economic Fields; Vol 10 No 2 (2019): TPREF, Volume X, Issue 2(20), Winter 2019, 2019)
The economic competition, which is becoming more and more fierce, imposes efficiency and performance on the economic environment. On the other hand, the rapid evolution of the technologies requires the continuous updating of the competences and of new forms of organization and management of the activity. In this dynamic context, managerial accounting becomes vital because it transforms organizations and exerts an influence on the social, economic and physical environment. In a thorough investigation of the problems it is observed that there is a certain perception of the companies, to act and react, to make decisions and to use systems different from the existing models, especially American and Japanese, which are often difficult to describe formalized, but which exists. On the other hand, there are differences between European countries. The management-specific tools are identical but do not apply equally in practice.